ANALISIS PERMINTAAN AYAM POTONG (BROILER) OLEH PEOAGANG PENGECER DAN TINGKAT KONSUMSI RUMAH TANGGA TERHADAP DAGING AYAM POTONG 01 KOTA BENGKULU - Purwoko, Agus; Romdon, M Mustopa; Subagio, . (Jurnal AGRISEP, 2004)
The objectives  of this research  were to analyze  factors  influencing  broiler meat demanded  by retailers   and  households.    The  research   was  conducted   at  Pasar  Minggu,     Bengkulu   city.   Two sampling  methods  were used,i.e,  Simple  Random  Sampling  for selecting  29 retailers  and Accidental Sampling  for selecting  58 households   (two  households   for each  retailer).  Multiple  regression  model which then estimated  with OLS was applied  in estimating  the objectives.   Results  showed  that factors partially   influencing   retailer'  demand  for broiler  meat  were  broiler  price  at producers/distributors     (X3) and  capital  (X6), while  broiler  meat  price  at  consumers   (X4) and  plastic  bag  price  (X5) were  not significant   factors.    At  household   level,    family  members   (X2), total  familiy  income  (X3) and  broiler meat  price  (X4) were  significantly   influencing  households  to consume  broiler  meat,  while  household education  ataianment   (X1), domestic  chicken  (buras)   meat price  (X5), tempe  price  (X6) and gold  fish price  (X7) were not.